Acrylic adhesive film with high damping coefficient for acoustics and preparation method of acrylic adhesive film

By adding specific components to the acrylic adhesive film, an acoustic adhesive film with high damping coefficient and high elastic modulus was developed, which solved the problems of low loudness and secondary bonding of existing materials in miniaturized electronic products, and achieved higher structural stability and usage yield.

CN119875543APending Publication Date: 2025-04-25CYBRID TECHNOLOGIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411945933.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing composite materials cannot meet the performance requirements of high damping coefficient and high elastic modulus in miniaturized electronic products, resulting in low loudness of diaphragm products and prone to secondary bonding problems during laser die cutting.

Method used

A high-dampening coefficient acrylic film for acoustics is developed. By adding acrylic resin with low Tg, high loss factor and high elastic modulus to the coating solution, a specific ultraviolet absorber, an epoxy resin curing agent and solvent, acrylic film with high damping performance and high elastic modulus is formed, and secondary bonding is prevented by using the ultraviolet absorber during laser die cutting.

Benefits of technology

The film with high damping coefficient and high elastic modulus is realized, which can effectively absorb and dissipate vibration energy, reduce vibration and noise, improve structural stability, and prevent secondary bonding at the film cross-sectional position in the post-processing section, improving the yield of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875543A_ABST
    Figure CN119875543A_ABST
Patent Text Reader

Abstract

The invention discloses an acrylic adhesive film with a high damping coefficient for acoustics. The acrylic adhesive film sequentially comprises a first release film, an acrylic adhesive layer and a second release film from top to bottom, the acrylic adhesive layer is obtained by drying an adhesive coating solution, and the coating solution comprises the following components in parts by weight: 40-80 parts of acrylic resin, 0.1-3 parts of an ultraviolet absorbent, 40-60 parts of a solvent and 0.2-3 parts of a curing agent. The high-damping-coefficient acrylic adhesive film for acoustics disclosed by the invention has various properties of a conventional acoustic acrylic adhesive film; the damping performance is excellent, the elastic modulus is high, the energy dissipation capacity is good, and the structural stability is high. And meanwhile, the special ultraviolet absorbent is synchronously added, so that secondary bonding of an adhesive layer at the section position is avoided after laser die cutting is carried out on a post-processing section, and actual use is facilitated. And in a composite material of an acoustic diaphragm or a miniature sound production device, the composite material has performance superior to that of a traditional acrylic adhesive film for acoustics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of acrylic adhesive films, and in particular relates to an acrylic adhesive film with a high damping coefficient for acoustics and a preparation method thereof. Background Art

[0002] In recent years, with the development of modern science and technology, people have higher and higher requirements for working and living environments, and vibration and noise control has become an urgent problem that needs to be solved.

[0003] With the rapid development of electronic technology, electronic products are increasingly widely used, especially miniaturized electronic products, such as mobile phones, IPADs, smart watches, smart headphones and other personal consumer electronic products. The market is becoming more and more popular. In these electronic products, micro sound devices are indispensable. At present, the diaphragms used in micro sound devices mostly use multi-layer composite materials, such as engineering plastics such as polyetheretherketone (PEEK), polyarylate (PAR), polyetherimide (PEI), polyimide (PI), thermoplastic polyurethane elastomer (TPU), thermoplastic polyester elastomer (TPEE) and other elastomeric materials and film materials such as acrylic film and silicone film. However, with the rapid development of small electronic products, electronic devices need to be equipped with micro sound devices with smaller size and better comprehensive performance. This demand has led to the inability of existing composite materials to meet performance requirements.

[0004] For example, engineering plastics such as PEEK and PAR have good temperature resistance, but the material resilience is poor, the product is prone to film folding, and cannot play a waterproof role. Elastomer materials such as TPU and TPEE have low melting points and poor temperature resistance. Although silicone rubber has good thermal stability and resilience, due to its symmetrical chemical structure, high stereoregularity, and small steric hindrance of symmetrically substituted methyl groups, the modulus or hardness of silicone rubber is relatively low, which in turn leads to low damping of the material, resulting in large product distortion of silicone rubber diaphragms. Acrylic materials are widely used in coatings, adhesives, fabric finishing agents, etc. due to their excellent light resistance, weather resistance, acid and alkali resistance, corrosion resistance, and mechanical properties, and can be used as damping materials for diaphragms of micro-sound devices; however, acrylic materials have a high density, resulting in a large mass of the diaphragm, resulting in a low loudness of the diaphragm product. In addition, in the actual laser die-cutting of the current acrylic materials in the post-processing section, secondary bonding of the adhesive layer at the cross-section position after die-cutting is prone to occur, resulting in secondary loss.

[0005] The laser wavelength used for film slitting by laser die-cutting machines is usually in the ultraviolet band, and the specific wavelength range is approximately between 280nm-360nm. According to the laser wavelength range, ultraviolet absorbers with specific ultraviolet absorption bands are added to improve the secondary loss in laser die-cutting in the post-processing stage.

[0006] Therefore, developing an acrylic film that is easy to post-process, has a high damping coefficient and a high elastic modulus is an urgent problem to be solved in this field. Summary of the invention

[0007] The purpose of the present invention is to provide an acrylic film with a high damping coefficient for acoustics, and specifically to provide an acrylic film with a high damping coefficient that is convenient for efficient post-processing, has various properties of conventional acoustic acrylic films, and has excellent damping performance and high elastic modulus, and has good energy dissipation capacity and high structural stability.

[0008] To achieve the above object, the technical solution adopted by the present invention is: an acrylic adhesive film with a high damping coefficient for acoustics, wherein the acrylic adhesive film comprises a first release film, an acrylic adhesive layer and a second release film from top to bottom;

[0009] The acrylic adhesive layer is obtained by drying an adhesive coating liquid, wherein the coating liquid comprises the following components in parts by weight:

[0010] 40-80 parts of acrylic resin, 0.1-3 parts of ultraviolet absorber, 40-60 parts of solvent, and 0.2-3 parts of curing agent.

[0011] The technical solution further improved in the above technical solution is as follows:

[0012] 1. In the above scheme, the Tg of the acrylic film is required to be -38±5°C, the loss factor peak is required to be greater than 1.25, the storage modulus corresponding to the loss factor peak is greater than 0.5MPa, and the absorbance in the ultraviolet absorption band of 280-380nm is required to be greater than 1.2.

[0013] 2. In the above scheme, the acrylic resin is selected from acrylic resins with low Tg, high loss factor and high elastic modulus, with Tg requirement of -38±5°C, loss factor peak requirement of greater than 1.2, and storage modulus corresponding to loss factor peak value greater than 0.45MPa. Among them, low Tg makes the material have better wettability, and high loss factor can make the material have better damping performance, can effectively absorb and dissipate vibration energy, and is suitable for applications that need to reduce vibration and noise. High loss modulus makes the material have good rigidity and hardness, can keep the shape unchanged when subjected to large external forces, and is not prone to permanent deformation.

[0014] 3. In the above scheme, the selected ultraviolet absorber is an ultraviolet absorber activated under a specific 270-380nm wavelength light source, and the ultraviolet absorber can be one of salicylate, benzophenone, benzotriazole and other types of ultraviolet absorbers. By adding ultraviolet absorbers to the formula system, during the laser die-cutting in the post-processing stage, it absorbs and consumes part of the ultraviolet light energy, promotes further cross-linking of the cross-section of the film, and prevents secondary bonding of the cross-section of the film after die-cutting.

[0015] 4. In the above scheme, the selected curing agent is preferably an epoxy resin curing agent, preferably an addition-type polyamine curing agent, which can be one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine or other fatty amines and aromatic amines.

[0016] 5. In the above scheme, the solvent selected is one or a mixture of ethyl acetate, ethyl formate, toluene, butanone, isobutyl acetate, and methyl acetate.

[0017] 6. In the above solution, the first release film is a silicone oil release film, and the silicone oil release layer has a release force of 3-50 gf / 25 mm and a thickness of 20-75 μm.

[0018] 7. In the above solution, the second release film is a silicone oil release film, and the release force of the silicone oil release layer is 6-100 gf / 25mm and the thickness is 25-100 μm.

[0019] 8. In the above solution, the release force of the first release film: the release force of the second release film is ≈1:2.

[0020] To achieve the above-mentioned purpose, another technical solution adopted by the present invention is: a method for preparing an acrylic film with a high damping coefficient for acoustics, comprising the following steps: mixing acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent in a certain proportion and stirring them evenly to obtain a coating liquid, using a second release film to transfer the coating liquid, applying an acrylic layer of a specific thickness and then attaching the first release film, and rolling up to obtain an acrylic film product.

[0021] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0022] 1. The acrylic film with high damping coefficient for acoustics provided by the present invention has excellent properties of low Tg, high loss factor and high elastic modulus.

[0023] Compared with traditional acrylic films for acoustics, it has higher damping performance. While having good wettability, it can also absorb and dissipate vibration energy, effectively reduce vibration and noise, improve structural stability, and prevent secondary bonding of the film cross section during laser die-cutting to improve the yield rate.

[0024] 2. The acoustic high damping coefficient acrylic film of the present invention has various properties of conventional acoustic acrylic films, and has excellent damping performance and high elastic modulus. It has good energy dissipation capacity and high structural stability. It also has excellent appearance and thickness uniformity. A specific ultraviolet absorber is added to it so that there will be no secondary bonding of the cross-section adhesive layer after laser die-cutting in the post-processing stage, which is convenient for practical use. The acoustic high damping coefficient acrylic film has better performance than traditional acoustic acrylic films in composite materials of acoustic diaphragms or micro-sound-generating devices, and can be widely used in the field of acoustics. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Attached Figure 1 It is a schematic diagram of the structure of the acrylic film with high damping coefficient of the present invention;

[0026] Attached Figure 2 A modulus test curve diagram of the high damping coefficient acrylic film provided in Example 1 of the present invention;

[0027] Attached Figure 3 The Tg curve of the high damping coefficient acrylic film provided in Example 1 of the present invention is tested using DSC. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with embodiments:

[0029] An acrylic adhesive film with a high damping coefficient for acoustics, characterized in that: the acrylic adhesive film comprises a first release film 1, an acrylic adhesive layer 2 and a second release film 3 from top to bottom; the acrylic adhesive layer 2 is obtained by drying an adhesive coating liquid.

[0030] Embodiment 1:

[0031] An acrylic resin with a Tg of -38.6°C, a peak loss factor of 1.24, and a loss factor peak corresponding to a storage modulus of 0.52 MPa was selected.

[0032] The UV absorber is benzotriazole, and the commonly used UV absorber UV-327 on the market is selected, and the UV absorption band is 270-380nm. The curing agent is the fatty polyamine curing agent in the epoxy resin curing agent, and the Yarui Chemical β-ethylethylenediamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0033] The above preferred acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 50:1:1:60 to obtain a finished glue. The finished glue is coated with a 36μm second release film 3, and then a 20μm thick acrylic adhesive layer 2 is coated and attached with a 25μm first release film 1, and the acrylic adhesive film product is rolled up.

[0034] The conventional performance of the acrylic film and the Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -38.4℃, the measured loss factor peak was 1.29, the storage modulus corresponding to the loss factor peak position was 0.58MPa, and the measured absorbance was 1.41.

[0035] Embodiment 2:

[0036] The acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent selected in Example 1 are mixed in a ratio of 60:2:1:50, and an acrylic adhesive film product is obtained according to the same preparation method as in Example 1.

[0037] The conventional properties of the acrylic film and its Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -38.1°C, the measured loss factor peak was 1.28, the storage modulus corresponding to the loss factor peak position was 0.56MPa, and the measured absorbance was 1.56.

[0038] Embodiment 3:

[0039] An acrylic resin with a Tg of -34.7°C, a peak loss factor of 1.21, and a loss factor peak corresponding to a storage modulus of 0.47 MPa was selected.

[0040] The UV absorber is benzotriazole, and the commonly used UV absorber UV-327 on the market is selected, and the UV absorption band is 270-380nm. The curing agent is the fatty polyamine curing agent in the epoxy resin curing agent, and the Yarui Chemical β-ethyldiethylenetriamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0041] The above preferred acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 60:1:0.6:60 to obtain a finished glue. A 50 μm second release film 3 is used to coat the finished glue. After coating a 30 μm thick acrylic adhesive layer 2, a 36 μm first release film 1 is attached and rolled up to obtain an acrylic adhesive film product.

[0042] The conventional properties of the acrylic film and its Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -35.1°C, the measured loss factor peak was 1.32, the storage modulus corresponding to the loss factor peak position was 0.52MPa, and the measured absorbance was 1.34.

[0043] Embodiment 4:

[0044] An acrylic resin with a Tg of -41.2°C, a peak loss factor of 1.21, and a loss factor peak corresponding to a storage modulus of 0.47 MPa was selected.

[0045] The UV absorber is benzotriazole, and the commonly used UV absorber UV-327 on the market is selected, and the UV absorption band is 270-380nm. The curing agent is the fatty polyamine curing agent in the epoxy resin curing agent, and the Yarui Chemical β-ethyldiethylenetriamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0046] The above preferred acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 40:3:2:60 to obtain a finished glue. A 50μm second release film 3 is used to coat the finished glue. After coating a 30μm thick acrylic adhesive layer 2, a 36μm first release film 1 is attached and rolled up to obtain an acrylic adhesive film product.

[0047] The conventional properties of the acrylic film and its Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -40.3°C, the measured loss factor peak was 1.28, the storage modulus corresponding to the loss factor peak position was 0.55MPa, and the measured absorbance was 1.86.

[0048] Embodiment 5:

[0049] The ultraviolet absorber UV-327 selected in Example 4 was adjusted to UV-234, and the rest was completely referred to Example 4 without any adjustment.

[0050] The conventional properties of the acrylic film and its Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -41.1°C, the measured loss factor peak was 1.27, the storage modulus corresponding to the loss factor peak position was 0.57MPa, and the measured absorbance was 1.72.

[0051] Comparative Example 1

[0052] An acrylic resin with a Tg of -26.2°C, a peak loss factor of 1.06, and a loss factor peak corresponding to a storage modulus of 0.32 MPa was selected.

[0053] The UV absorber is benzotriazole, and the commonly used UV absorber UV-327 on the market is selected, and the UV absorption band is 270-380nm. The curing agent is the fatty polyamine curing agent in the epoxy resin curing agent, and the Yarui Chemical β-ethylethylenediamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0054] The above preferred acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 50:1:1:60 to obtain a finished glue. The finished glue is coated with a 36μm second release film 3, and then a 20μm thick acrylic adhesive layer 2 is coated and attached with a 25μm first release film 1, and the acrylic adhesive film product is rolled up.

[0055] The conventional performance of the acrylic film, Tg, loss factor, storage modulus at the loss factor peak position, and absorbance in the 280nm-380nm band were tested. The measured Tg was -26.4°C, the measured loss factor peak was 1.08, the storage modulus corresponding to the loss factor peak position was 0.37MPa, and the measured absorbance was 1.40. Comparative Example 2:

[0056] An acrylic resin with a Tg of -38.6°C, a peak loss factor of 1.24, and a loss factor peak corresponding to a storage modulus of 0.52 MPa was selected.

[0057] No UV absorber is added, and the curing agent is the aliphatic polyamine curing agent among the epoxy resin curing agents, and the Yarui Chemical β-ethylethylenediamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0058] The above preferred acrylic resin, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 50:1:1:60 to obtain a finished glue. The finished glue is coated with a 36μm second release film 3. After coating a 20μm thick acrylic adhesive layer 2, a 25μm first release film 1 is attached and rolled up to obtain an acrylic adhesive film product.

[0059] The conventional performance, Tg, loss factor, storage modulus at the loss factor peak position, and absorbance in the 280nm-380nm band of the acrylic film were tested. The measured Tg was -38.7°C, the measured loss factor peak was 1.27, the storage modulus corresponding to the loss factor peak position was 0.57MPa, and the measured absorbance was 0.31. Comparative Example 3:

[0060] An acrylic resin with a Tg of -26.2°C, a peak loss factor of 1.06, and a loss factor peak corresponding to a storage modulus of 0.32 MPa was selected.

[0061] No UV absorber is added, and the curing agent is the aliphatic polyamine curing agent among the epoxy resin curing agents, and the Yarui Chemical β-ethylethylenediamine curing agent is selected. The solvent is the commonly used ethyl acetate.

[0062] The above preferred acrylic resin, epoxy resin curing agent and solvent are mixed and stirred in a ratio of 50:1:1:60 to obtain a finished glue. The finished glue is coated with a 36μm second release film 3. After coating a 20μm thick acrylic adhesive layer 2, a 25μm first release film 1 is attached and rolled up to obtain an acrylic adhesive film product.

[0063] The conventional properties of the acrylic film and its Tg, loss factor, storage modulus at the loss factor peak position and absorbance in the 280nm-380nm band were tested. The measured Tg was -26.4°C, the measured loss factor peak was 1.08, the storage modulus corresponding to the loss factor peak position was 0.37MPa, and the measured absorbance was 0.31.

[0064] Various performance test evaluations:

[0065] Tg: tested using differential scanning calorimeter (DSC) equipment;

[0066] Storage modulus: tested using a rheometer;

[0067] Loss factor: the ratio of loss modulus to storage modulus, tested using a rheometer;

[0068] Absorbance: Tested using a UV spectrophotometer;

[0069]

[0070] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An acrylic film with a high damping coefficient for acoustics, characterized in that: The acrylic adhesive film comprises, from top to bottom, a first release film (1), an acrylic adhesive layer (2) and a second release film (3); The acrylic adhesive layer (2) is obtained by drying an adhesive coating liquid, wherein the coating liquid comprises the following components in parts by weight: 40-80 parts of acrylic resin, 0.1-3 parts of ultraviolet absorber, 40-60 parts of solvent, and 0.2-3 parts of curing agent.

2. The high damping coefficient acrylic film for acoustics according to claim 1, characterized in that: The Tg of the acrylic adhesive film is -38±5°C, the loss factor peak is greater than 1.25, the storage modulus corresponding to the loss factor peak is greater than 0.5MPa, and the absorbance of the acrylic adhesive film in the ultraviolet absorption band of 280-380nm is greater than 1.

2.

3. The high damping coefficient acrylic film for acoustics according to claim 1 or 2, characterized in that: The acrylic resin is selected from acrylic resins with low Tg, high loss factor and high elastic modulus.

4. The high damping coefficient acrylic film for acoustics according to claim 3, characterized in that: The Tg of the acrylic resin is -38±5°C, the loss factor peak is greater than 1.2, and the storage modulus corresponding to the loss factor peak is greater than 0.45MPa.

5. The high damping coefficient acrylic film for acoustics according to claim 1 or 2, characterized in that: The selected ultraviolet absorber is an ultraviolet absorber activated under a specific 270-380nm wavelength light source, and the ultraviolet absorber can be one of salicylic acid esters, benzophenones, benzotriazoles and other types of ultraviolet absorbers.

6. The high damping coefficient acrylic film for acoustics according to claim 1 or 2, characterized in that: The curing agent is preferably an epoxy resin curing agent.

7. The high damping coefficient acrylic film for acoustics according to claim 6, characterized in that: The curing agent is an addition type polyamine curing agent, which is one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine or other fatty amines and aromatic amines.

8. The high damping coefficient acrylic film for acoustics according to claim 1, characterized in that: The acrylic adhesive layer (2) has a thickness of 10 to 100 μm; The first release film (1) is a silicone oil release film, the release force of the silicone oil release layer is 3 to 50 gf / 25 mm, and the thickness is 20 to 75 μm; The second release film (3) is a silicone oil release film, the release force of the silicone oil release layer is 6 to 100 gf / 25 mm, and the thickness is 25 to 100 μm.

9. The high damping coefficient acrylic film for acoustics according to claim 1, characterized in that: Release film (1) release force: release film (3) release force ≈ 1:

2.

10. A method for preparing the acrylic film with high damping coefficient for acoustics according to claim 1, characterized in that: The following steps are involved: Acrylic resin, ultraviolet absorber, epoxy resin curing agent and solvent are mixed and stirred in a certain proportion to obtain a coating liquid, and the coating liquid is transferred using a second release film (3). After coating an acrylic adhesive layer (2) of a specific thickness, the first release film (1) is attached and rolled up to obtain an acrylic adhesive film product.

Citation Information

Patent Citations

  • Acrylic vibrating diaphragm adhesive tape for loudspeaker and preparation method thereof

    CN111808537A

  • Environment-friendly acrylic PVC (polyvinyl chloride) protective film with low film tearing voltage and preparation method of environment-friendly acrylic PVC protective film

    CN114921188A

  • Ultraviolet light blocking optical adhesive film and preparation method thereof

    CN115746718A

  • Acrylate resin with high loss factor as well as preparation method and application thereof

    CN118667063A

  • High damping rubber composition and application of the same

    JP2011178962A